Cultural Changes Since Đổi Mới - From Guidelines to Reality - Nguyen-Manh, Dung (Journal of Urban Culture Research, 2022)
In Vietnam a couple years before the reform termed Đổi Mới, was a grey picture with serious crises. That is a vital premise, a life and death situation for the Communist Party of Vietnam in the VIth Party Congress in 1986. On the eve of Đổi Mới, Vietnamese culture in general, was in a narrow, dogmatic and ideologically subsidized environment. Yet, since Đổi Mới, the Vietnamese culture and the cultural development, although resulted in achievements, faces a huge challenge: restrictions, not yet suitable for its national conditions, socialist-oriented market economy and international integration. This article provides personal experiences and perspectives (on cultural change visually via observational and participatory research methods) comparing the before and after Đổi Mới while seeking to assess the cultural situation and the acculturation of Vietnam since Đổi Mới. The key questions are how Vietnamese culture has changed from guidelines of the Party to its social and cultural reality and how culture changed as seen and perceived from 1980s to present-day generation? In doing so, this article aims to address the general picture of transformation, vivid acculturation in accordance with the process of the economic, social and political Đổi Mới in Vietnam.